Food avoidance taboos during breastfeeding are widespread and associated with large declines in maternal dietary diversity in Myanmar - Headey, Derek D.; Tauseef, Salauddin; Linn, Khin Mar; Oo, Theingi; Nyi, Soe Nyi (Elsevier, 2025)
Background Maternal food avoidance practices during pregnancy and breastfeeding have been documented in several Asian countries, but their prevalence and impacts on dietary diversity are not well quantified.